2009
DOI: 10.1103/physrevb.79.165407
|View full text |Cite
|
Sign up to set email alerts
|

Electron-hole spectra created by adsorption on metals from density functional theory

Abstract: Nonadiabaticity in adsorption on metal surfaces gives rise to a number of measurable effects such as chemicurrents and exoelectron emission. Here we present a quantitative theory of chemicurrents on the basis of ground-state density functional theory ͑DFT͒ calculations of the effective electronic potential and the Kohn-Sham band structure. Excitation probabilities are calculated both for electron-hole pairs and for electrons and holes separately from first-order time-dependent perturbation theory. This is acco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Attempts to theoretically describe chemicurrents have been previously reported (21)(22)(23)(34)(35)(36)(37). In this work, we employed an FOM to obtain the energy spectrum of excited electrons that result from H/D atom collisions at the metal (21)(22)(23).…”
Section: Methodsmentioning
confidence: 99%
“…Attempts to theoretically describe chemicurrents have been previously reported (21)(22)(23)(34)(35)(36)(37). In this work, we employed an FOM to obtain the energy spectrum of excited electrons that result from H/D atom collisions at the metal (21)(22)(23).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the motion through the surface electron density, the situation is thus highly comparable to vibrational dynamics, an area where the LDFA has been shown to perform quantitatively [22]. Correspondingly, we expect this level of theory to provide a reliable assessment of the relative amount of electronic friction, even though it would be conceptually interesting to compare to higher-level theories that for instance account for tensorial aspects of friction [50] or that additionally provide the explicit ℎ-pair excitation spectra [12,51]. We further note that similar to the findings for adsorbate vibrations [22], a key element in the use of the simple LDFA scheme is the appropriate determination of the host embedding density experienced by the adsorbate.…”
mentioning
confidence: 99%
“…15 Motivated by this controversy, an important number of theoretical methods that include electronic excitations have been recently developed. [16][17][18][19][20][21][22][23][24] In some cases, non-adiabatic dynamics based on low-dimensional calculations has resulted in overestimation of the effects associated with e-h pair excitations. For example, for N 2 /Ru(0001) it was claimed, 16 based on low-dimensional non-adiabatic calculations, that the huge discrepancy between low-dimensional adiabatic calculations and experiment was mostly due to e-h pair excitations, whereas a subsequent adiabatic high-dimensional dynamics study 25,26 showed that most of the discrepancy vanishes when the six degrees of freedom of the molecule are taken into account in the dynamics.…”
Section: Introductionmentioning
confidence: 99%